2017
DOI: 10.1161/circimaging.116.005771
|View full text |Cite
|
Sign up to set email alerts
|

Right Heart End-Systolic Remodeling Index Strongly Predicts Outcomes in Pulmonary Arterial Hypertension

Abstract: Background Right ventricular (RV) end-systolic dimensions provide information on both size and function. We investigated whether an internally scaled index of end-systolic dimension is incremental to well-validated prognostic scores in pulmonary arterial hypertension (PAH). Methods and Results From 2005 to 2014, 228 patients with PAH were prospectively enrolled. RV end-systolic remodeling index (RVESRI) was defined by lateral length divided by septal height. The incremental values of RV free-wall longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 32 publications
1
65
0
Order By: Relevance
“…An index between 1.35 and 1.70 suggests adverse remodelling. An index !1.7 suggests severe adverse remodelling in the setting of pulmonary hypertension [26].…”
Section: Right Ventricular End-systolic Remodelling Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…An index between 1.35 and 1.70 suggests adverse remodelling. An index !1.7 suggests severe adverse remodelling in the setting of pulmonary hypertension [26].…”
Section: Right Ventricular End-systolic Remodelling Indexmentioning
confidence: 99%
“…Higher Tei index [43], greater right atrial area [24], larger inferior vena cava (IVC) diameter [44], lower TAPSE [44,45], higher estimated mean and diastolic pulmonary artery pressure [44], the degree of interventricular septal shift [44], right ventricular diameters [46], biventricular index [11] and right ventricular end-systolic remodelling ratio [26] have all been reported to be associated with adverse clinical outcomes in the setting of pulmonary hypertension. Right ventricular systolic to diastolic duration ratio is associated with poor outcome in paediatric pulmonary hypertension [21] and Eisenmenger's syndrome [22] but has not been studied in broader pulmonary hypertension settings.…”
Section: Prognostic Utility Of Echocardiography In Pulmonary Hypertenmentioning
confidence: 99%
“…Lastly prior studies have demonstrated RV size and function to be a critical prognostic indicator in pulmonary arterial hypertension (PAH) and congenital heart disease. 7,8,9,10 Despite the role of the RV in stratification of prognosis, non-invasive evaluation of the RV remains challenging due to several key anatomic factors.…”
Section: Right Ventricle Backgroundmentioning
confidence: 99%
“…8 Threedimensional echocardiography and speckle tracking imaging have been shown to predict RV failure and clinical outcome more accurately than 2D echocardiography in chronic pulmonary hypertension. 5,7 In this issue of Circulation: Cardiovascular Imaging, Amsallem et al 9 propose a new 2D echocardiography-derived RV end-systolic remodeling index (RVESRI) in patients with pulmonary arterial hypertension (PAH). Amsallem et al define the new RVESRI as the ratio of end-systolic RV lateral wall length to end-systolic septal height measured in the RV-focused apical 4-chamber view.…”
Section: See Article By Amsallem Et Almentioning
confidence: 99%